2002
DOI: 10.1097/00024382-200204000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Protect Liver from Ischemia-Reperfusion Injury by an Inducible Nitric Oxide Synthase-Dependent Mechanism

Abstract: The aim of this study was to investigate the role of nitric oxide (NO) in rat hepatic ischemia-reperfusion (I/R) injury. Animals were divided into four groups: Group I, control; Group II, gadolinium chloride (GdCl3), a Kupffer cell depleting agent, pretreated; Group III, S-methylisothiourea (SMT), a potent inducible NO synthase (iNOS) inhibitor, pretreated; Group IV, pretreated with SMT, then treated with S-Nitroso-N-acetylpenicillamine (SNAP), a NO donor, after ischemia. Sprague-Dawley rats underwent left lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 32 publications
0
52
0
2
Order By: Relevance
“…Complicated mechanisms and numerous molecules are involved in exerting the protective effects of NO against liver IRI, including ATP molecules, endothelin, adhesion molecules, cytokines, free radical species, and antioxidants [33] (Figure 2). NO has been shown to potentiate hepatic ATP levels, reduce oxidative damage, prevent the reduction of antioxidants such as glutathione, and reduce the adverse effects of endothelin during liver IRI [33,34] . Studies have demonstrated that NO affects cellular decisions of life and death by either turning on or shutting off apoptotic pathways, suggesting that NO can function differently depending on the dose and duration of exposure [35,36] .…”
mentioning
confidence: 99%
“…Complicated mechanisms and numerous molecules are involved in exerting the protective effects of NO against liver IRI, including ATP molecules, endothelin, adhesion molecules, cytokines, free radical species, and antioxidants [33] (Figure 2). NO has been shown to potentiate hepatic ATP levels, reduce oxidative damage, prevent the reduction of antioxidants such as glutathione, and reduce the adverse effects of endothelin during liver IRI [33,34] . Studies have demonstrated that NO affects cellular decisions of life and death by either turning on or shutting off apoptotic pathways, suggesting that NO can function differently depending on the dose and duration of exposure [35,36] .…”
mentioning
confidence: 99%
“…On the other hand, in response to enhancement of oxidative stress, cells undergo specific changes in enzyme activities, cytoskeletal structure, membrane transport, antioxidant defenses, and induction of heat shock protein, among which heme oxygenase (HO)-1 is believed to play a key role (14,37). The HO system is among the most critical of the cytoprotective mechanisms activated during cellular stress, hyperthermic preconditioning, or long-term fasting, exerting antioxidant and anti-inflammatory functions, acting as a molecular chaperon, modulating cell cycle, and maintaining microcirculation (3,9,20).…”
mentioning
confidence: 99%
“…There is growing evidence that Kupffer cells play a critical role in regulating immune functions following trauma (25,29). Located in the liver sinusoids, Kupffer cells represent the largest population of tissue-fixed macrophages in the body and play a key role in the recognition and eventual clearance of bacteria from the blood (46).…”
mentioning
confidence: 99%